PENINGKATAN SIKAP DAN KEBIASAAN BELAJAR POSITIF DENGAN MENGGUNAKAN TOKEN ECONOMY PADA SISWA KELAS V SD NEGERI 4 WAY GALIH KECAMATAN TANJUNG BINTANG TAHUN PELAJARAN 2012/2013 - Rika Yuniarti; Yusmansyah Yusmansyah; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The Problem of this research was that student’s attitudes and positive learning habits are low. Research problem of this research is “could student’s attitudes and positive learning habits be increased by using token economy?”. The purpose of this research was to know that student’s attitudes and positive learning habits were could increaseds by using token economy. The Method of this research was quasi experimental method teqhnique of the one group pretest-posttest desin. The Subject of this research were 6 students who had low of attitudes and positive learning habits. Technique in gaining the data of this research were by using observation. Result of this research showed that the student’s attitudes and positive learning habits could reduce by using token economy, it showed from the data analysis that use t-test, from the result of pretest and posttest gaining tarithmathic=15,36 ttable=2,015 so, Ho was rejected and Ha was received, it means that student’s attitudes and positive learning habits could increased by using token economy. Conclusion of this research were student’s attitudes and positive learning habits could increased by using token economy for  students grade V SD Negeri 4 Way Galih Subdistrict Tanjung Bintang Year of 2012/2013. The suggestions were (1) for teacher, please give program of guidance for inform about how infortant studen’ts attitudes and positive learning habits and how did to increasing it. (2) for parent, please standing behind and apply effort increasing of student’s attitudes and positive learning habits for students when to home after got the information from teachers. (3) for researchers, in this research token economy is not suited for students who had social phobia, so researcher should to research students who had social phobia by using systematic desensitisasi. Key word: token economy, attitudes and positive learning habits